Preparation of High Al Content (AlxGa1−x)2O3 Films by Low-Pressure Reactive Vapor Deposition on Sapphire Substrates. (4th May 2020) - Shi, Jianjun; Liang, Hongwei; Xia, Xiaochuan; Long, Ze; Zhang, Heqiu; Liu, Yang; Dong, Xin; Jia, Zhitai
Abstract : Beta-(Alx Ga1−x )2 O3 thin films were prepared on c-plane sapphire substrates by low-pressure reactive vapor deposition at different temperature. The crystal structure, surface morphology, and optical properties of β -(Alx Ga1−x )2 O3 films were investigated by X-ray diffraction (XRD), scanning electron microscope (SEM), atomic force microscope (AFM), X-ray photoelectron spectroscopy (XPS), and transmission spectra. The β -(Alx Ga1−x )2 O3 films were preferred [ 2 ̄ 01] orientation. The film grown at 1400 °C has narrower full width half maximum (FWHM) than grown at 1450 °C. As the growth temperature increases, the Al group decreases. The Al content of β -(Alx Ga1−x )2 O3 films grown at 1400 °C and 1450 °C are x = 0.524 and x = 0.489, respectively. The SEM and AFM images showed different growth mode for β -(Alx Ga1−x )2 O3 films grown at 1400 °C and 1450 °C and their root-mean-square roughness (RMS) values are 5.27 nm and 5.33 nm, respectively. All the prepared β -(Alx Ga1−x )2 O3 films have high transmittances exceeding 90% in visible region and large optical bandgap above 6 eV. These results indicate that low-pressure reactive vapor deposition technology is a promising growth technology for a high quality β -(AlGa)2 O3 films with tunable properties.